MAKE. Robot r-r-rumble! - Senese, Mike, 1975- (MAKE COMMUNITY, LLC, 2022)
Put your bot-building skills to the test by going head-to-head with your best pals in radio-controlled, weapon-laden robot combat ... It's Robot Rumble time! From antweight to heavyweight, we show you what you need to know to build, fight, and WIN! Get an overview of popular combat robot types and the best starter kits, or jump right in with step-by-step instructions to build your first antweight combat robot for cheap! Learn expert tips for victory in the arena, and go behind the scenes to see what it takes to start a combat robot league from the ground up. Plus, 53 projects and tips including: Hack your sleep with a wearable dream incubator Hot-rod a K40 laser cutter with hacks and mods Light up your outfit or costume with wireless, inductive LEDs Build a musical drum robot as a doorbell or MIDI instrument And much more!.